2021
DOI: 10.1007/s11030-021-10230-6
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis and identification of antiviral coumarin derivatives against 3-chymotrypsin-like main protease of the novel coronavirus SARS-CoV-2

Abstract: Coronavirus disease 2019 (COVID-19) is a pandemic viral disease caused by SARS-CoV-2 that generated serious damages for both the human population and the global economy. Therefore, it is currently considered as one of the most important global health problems of human societies and there is an urgent need for potent drugs or vaccines which can effectively combat this virus. The chymotrypsin-like protease (3CLpro) of SARS-CoV-2 plays a key role in the viral replication inside the host and thus is a promising dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
(70 reference statements)
1
19
0
Order By: Relevance
“…molecular docking, molecular dynamics simulation, ADMET prediction, and MM-PBSA binding energy calculation. 87 This investigation revealed that inophyllum P (74), mesuol (75), oxypeucedanin (76), and glycycoumarin (77) showed the highest binding affinity with the best negative energy scores (Figure 18), and they interacted with one or both of His41 and Cys145 residues of 3CLpro through hydrophilic and hydrophobic bonding. 87 These coumarins also had good pharmacokinetics, as well as drug-likeness.…”
Section: Antiviral Alkaloids and Alkaloid-like Compounds Against Covi...mentioning
confidence: 90%
See 2 more Smart Citations
“…molecular docking, molecular dynamics simulation, ADMET prediction, and MM-PBSA binding energy calculation. 87 This investigation revealed that inophyllum P (74), mesuol (75), oxypeucedanin (76), and glycycoumarin (77) showed the highest binding affinity with the best negative energy scores (Figure 18), and they interacted with one or both of His41 and Cys145 residues of 3CLpro through hydrophilic and hydrophobic bonding. 87 These coumarins also had good pharmacokinetics, as well as drug-likeness.…”
Section: Antiviral Alkaloids and Alkaloid-like Compounds Against Covi...mentioning
confidence: 90%
“…87 This investigation revealed that inophyllum P (74), mesuol (75), oxypeucedanin (76), and glycycoumarin (77) showed the highest binding affinity with the best negative energy scores (Figure 18), and they interacted with one or both of His41 and Cys145 residues of 3CLpro through hydrophilic and hydrophobic bonding. 87 These coumarins also had good pharmacokinetics, as well as drug-likeness. An independent docking analysis also revealed that glycycoumarin (77) and isodispar B (78) were promising coumarins against COVID-19 virus (Figure 18).…”
Section: Antiviral Alkaloids and Alkaloid-like Compounds Against Covi...mentioning
confidence: 90%
See 1 more Smart Citation
“…Several studies have shown that essential oils from medicinal plants, including Citrus spp., Hyssopus officinalis, Illicium spp., mayweeds, tea trees, Mentha spp., Santalum spp., Pinus spp., and certain other aromatic plants, have antiviral properties [258]. Essential oils have the ability to penetrate the lipid bilayer layer of the viral envelope in an abrupt manner, altering the fluidity of the membrane [275]. Because of their lipophilic character, monoterpenes, oxygenated sesquiterpenes, and phenylpropanoids in essential oils can disturb the phospholipid bilayer barrier of human coronaviruses, interfering with the shape of the proteins of enveloped virus throughout the infection [276].…”
Section: Natural Compounds From Plants and Sars-cov-2mentioning
confidence: 99%
“…The key druggable target of SARS-CoV-2 involves 3-chymotrypsin-like protease (3CL pro ) [39,40], papainlike protease (PL pro ) [41][42][43][44], RNA-dependent RNA polymerase [45], and spike (S) proteins [46,47]. In this work, 6LU7, main protease (M pro ) of COVID-19, crystallized by Liu et al (2020), is used as a potential protein target for the phytochemicals selected.…”
Section: Introductionmentioning
confidence: 99%